Dyscalculia in malaysia: awareness, assessment and intervention - Hashim, Noor Hasanah; Mahat, Jazihan; Mohd Ayub, Ahmad Fauzi Bin; Syed Abdullah, Sharifah Intan Sharina (Universiti Putra Malaysia, 2024)
Dyscalculia, a specific learning disability affecting mathematical abilities, is a significant but often overlooked issue in Malaysia. This study provides an analysis of dyscalculia in the Malaysian context. By exploring on awareness and assessment for dyscalculia helps to understand in developing a mobile application for intervention to help struggling pupils in mathematical concepts as well as reaching the SDG 4 in bringing quality education. Awareness of dyscalculia among educators, parents, and educational psychologists in Malaysia is limited compared to other learning disabilities such as dyslexia. This lack of awareness can lead to undiagnosed cases and inadequate support for individuals struggling with mathematical concepts. Efforts to raise awareness through various empirical study, educational campaigns, professional development programs, and parent workshops are essential to ensure early identification and intervention for those affected by dyscalculia. Assessment of dyscalculia in Malaysia is typically carried out by educational psychologists or special education professionals using standardized tests and observations. However, based on this study interview, dyscalculia is often undiagnosed and overlooked. Collaborative efforts between researchers, educators, educational psychologist and policymakers are crucial to provide validate assessment measures that accurately identify dyscalculia in Malaysian students. Developing mobile application as an intervention is a strategy for dyscalculia in Malaysia that encompass a multidisciplinary approach involving educators, psychologists, speech therapists, and occupational therapists. Evidence-based interventions such as tailored math programs, multisensory learning techniques, and cognitive-behavioral therapy have shown promising results in improving mathematical skills and self-confidence in individuals with dyscalculia. Furthermore, inclusive education practices and assistive technologies such as mobile application can enhance the learning experience for students with dyscalculia in mainstream classrooms. In conclusion, addressing dyscalculia in Malaysia requires a comprehensive approach that encompasses awareness, assessment, and intervention strategies. By increasing awareness, providing validate sensitive assessment tools, and implementing a mobile application as interventions, Malaysia can better support individuals with dyscalculia and empower them to reach their full potential in mathematics and beyond.